An appraisal of the provision of "benefits" as an unfair labour practice in South African labour law - Newaj, Kamalesh (University of Pretoria, 2019)
This thesis seeks to resolve the ambiguities surrounding the use of the unfair labour practice relating to the provision of “benefits” as a dispute resolution mechanism in South African labour law. This mechanism has been plagued with uncertainty, primar-ily because of the lack of a statutory definition of benefits. Evidently, the interpretation and application of benefits have been left to the courts, resulting in two diverse ap-proaches being endorsed. The first one sought to confer a narrow connotation on ben-efits, the rationale being to separate benefits from the definition of “remuneration”. It further sought to limit the use of this unfair labour practice to instances where the benefit claimed was exclusively provided for ex contractu or ex lege. The primary ob-jective was to protect the divide between disputes of right and disputes of interest, a distinction that is recognised and encouraged in our law. The second approach was one that fostered an expansive interpretation of the term, deeming it to be part of re-muneration. Needless to say it resulted in countless items being subject to determina-tion as benefit disputes. Furthermore, it extended benefits beyond those rooted in con-tract or legislation, including those granted or offered subject to the exercise of mana-gerial discretion. The supplementary challenges firstly relate to the absence of statutory direction on the standards of fairness to be applied in evaluating employer conduct. Secondly, the judiciary has provided opportunities for employees to utilise recourse other than the unfair labour practice provisions to address benefit disputes. Such leeway comes in the form of contractual recourse as well as the ability to institute strike action. In search of solutions to the problems identified above, the study explores and anal-yses the history of the unfair labour practice concept. Thereafter, an extensive exam-ination of the developments in this area of the law is undertaken. This includes a com-prehensive analysis of legislation, case law and academic writings. Having docu-mented and analysed the South African position both pre- and post-democracy, the study critically evaluates these sources of law. The study further involves a diagnostic assessment of international legal instruments and foreign law in order to extract best practices. The conclusions reached are, firstly, that an expansive interpretation of benefits is warranted. This is in line with a purposive interpretation of the LRA, which promotes the constitutional right to fair labour practices and international law. This study there-fore proposes a wide-ranging definition of the term benefits. Secondly, standards of substantive and procedural fairness have been found to be applicable in evaluating employer conduct. As such, fairness guidelines based on these standards have been developed. Thirdly, in respect of the alternate avenues available to resolve benefit disputes, it has been found that although there are strong indicators that point to a conclusion that contractual recourse has been supplanted by statutory recourse, such a finding cannot be definitively made. Furthermore, section 64(4) as it stands provides for the right to strike over unilateral changes to terms and conditions of employment, which includes unilateral changes to pre-existing benefits. However, the judiciary can limit the use of this section in benefit disputes by prioritising the substance of the dis-pute over its form. This thesis ultimately proposes the incorporation of a Code of Good Practice into the LRA. The Code of Good Practice: Benefits adopts the principal research findings of this study. It encourages the enforcement of benefit disputes through the dispute res-olution institutions set up by the LRA. The adoption of this Code (The Code of Good Practice: Benefits) will bring certitude to this field of labour law.
Keywords: Labour law; Labour practice; South Africa

The regulation of non-standard employment in Southern Africa : the case of South Africa with reference to several other SADC countries - Mokofe, William Manga (University of South Africa, 2018)
This doctoral thesis deals with the regulation of non-standard employment in Southern Africa: the case of South Africa with reference to several other SADC countries. The growth and presence of non-standard employment since the 1970s has revealed an important concern in a number of countries, both at the global and national levels. The overall significance of non-standard employment has increased in recent decades in both developed and developing states, as its use has grown exponentially across economic sectors and employment. Non-standard employment is the opposite of the standard employment relationship, which is work that is full time and indefinite. Non-standard employment includes an unequal employment relationship between an employee and an employer. Some workers choose to work in non-standard employment, and the choice has positive results. Nonetheless, for the majority of workers, non-standard employment is associated with job insecurity, exploitation, and the absence of trade unions and collective bargaining. Non-standard employment can also create challenges for firms, the labour market and the economy, including society at large. Backing decent work for all entails a comprehensive understanding of non-standard employment and its ramifications. This study explores the regulation and protection of non-standard employment in Southern Africa with focus on South Africa. The study draws on international and regional labour standards, the South African Constitution of 1996, and the national experience to make policy recommendations that will ensure workers are protected, firms are sustainable and labour markets operate well. Social justice and the democratisation of the workplace cannot be achieved if workers in non-standard employment are excluded from the labour relations system.
Keywords: Collective bargaining; Labor laws and legislation; Non-standard employment; Part-time employment; South Africa; Standard employment; Temporary employment; Temporary workers; Vulnerable workers

The integration of work and parenting: a comparative legal analysis - Rossouw, Elzaan (Stellenbosch University, 2018)
Given the importance of parental care to children, parents and broader society and the apparent conflict between work and adequate parental care, this study evaluates the legal facilitation of the integration of work and care across nine countries, including South Africa. The study recognises that legal operationalisation of the integration of work and care primarily takes place at domestic legislative level and shows that this happens against the backdrop of widespread recognition of the importance of the family and care at the international, regional and constitutional levels. The study builds on the reality that domestic legislation in this context consists of (a combination of) equality law and specific rights contained in employment standards legislation. The comparative review of equality law as applied in the area of the work-care conflict shows that, despite the potential and promise that equality law holds to facilitate the integration of work and care, this potential has not been realised and probably will not be in future. This necessarily shifts the focus to an approach founded on the extension of specific rights related to time off or leave, as well as flexible working, to employees in order to enable them effectively to combine work and caregiving. The comparative review of specific rights in this area leads to the conclusion that South Africa lags far behind certain developed and comparable developing countries in its legislative recognition of the importance of caregiving and in its subsequent level of employment rights extended to caregivers. Given the ample room for improvement, suggestions for legislative reform are made based on the comparative experience of other countries
Keywords: Child care services; Comparative law; Employee rights; Employment standards; Equity; Labour law; Labour legislation

Finding innovative solutions to extend labour law and social protection to vulnerable workers in the informal economy - Fourie, E. (North-West University, 2018)
The world of work has changed and this includes its fundamental design, purpose and coverage of employment. Work in the informal economy has increased and in many developing and middle income countries, work in the informal economy is the norm. In South Africa as well as in other developing countries informal economy workers do not enjoy sufficient protection in terms of labour and social protection measures. These workers are not recognised, regulated or protected by labour legislation or social protection measures and can be characterised by varying degrees of dependency and vulnerability. In countries where the informal economy is increasingly creating a parallel economic world to that of the formal economy, the extension of protection by facilitating the ability of these workers to bargain collectively and the role of national and local governments become increasingly important. Women workers in the informal economy are particularly vulnerable and face discrimination on multiple grounds and levels as gender inequalities in the informal economy cut across race and class lines. Linkages between informality, gender and poverty exists, namely: the poor are more likely to work in the informal economy; more poor women than non-poor women work in the informal economy and that there is a gender gap in earnings in the informal economy as women were earning less than their male counterparts and were less likely to be organised and have social protection. It is of the utmost importance that labour and social legislation accommodates and extends protection to informal economy workers. The larger the informal economy becomes, the greater the need becomes for social and labour protection. It will be impossible to provide these workers with the protection they deserve without legislative intervention. Furthermore, this intervention must be innovative and tailor-made to successfully extend labour and social protection to informal economy workers. When considering the protection of these workers it is also of importance to explore the design and implementation of innovative and tailor-made solutions, considering for example the nature of their work and their workplace. The focus of this study is specifically on distinctive vulnerable categories of women workers in the informal economy who are without adequate labour and social protection. These categories are domestic workers, informal traders and waste pickers. It is important to consider lessons learnt in other jurisdictions to adequately address the challenges in the informal economy. This study considers interventions in two leading developing jurisdictions, namely India and Brazil. Both these countries have a high prevalence of informal workers with inadequate labour and social protection. Labour law must thus meet the challenges posed by the realities of new forms of work. The important function of labour law to protect and promote the human dignity of workers will often result in a cross-over of various subsystems of the law. If we consider human dignity as an important component of labour law, then we need to consider an interdisciplinary approach and the promotion of such an approach. This approach will mean that labour law can no longer function in isolation and other branches of the law, such as social security law, corporate law, human rights and family law will increasingly have an impact on the human dignity of workers. When considering the future of labour law and specifically in relation to the labour and social protection of women in the informal economy, it is vital that the new framework is intrinsically linked to concepts such as democracy, social justice, freedom, and human rights. International and regional institutions are playing an increasingly important role in the empowerment of women, the promotion of equality and decent work for all women. This study identifies and critically considers the relevant international institutions and instruments, the impact of international standards, regional institutions and regional labour standards, particularly those of the African Union (AU) and the Southern Africa Development Community (SADC), and other global initiatives directed at the social and labour protection of women workers in the informal economy. The South African position with reference to domestic workers appears to provide an adequate regulatory framework in respect of the regulation of these workers; however, in practice there are various challenges, including the enforcement of the legislative provisions and a disregard for the notion of substantive equality. Although domestic workers enjoy some protection, waste pickers and informal traders as own-account workers without a distinctive employee-employer relationship are excluded from most labour and social protection measures and innovative and tailor-made solutions are required. The regulation of waste pickers and informal traders in South Africa is fragmented and lacks comprehensive and uniform legislation is absent. Voice and representation is of paramount importance to these women to ensure decent work. Enabling frameworks must be established to promote this. One of the most important objectives of organisation for women workers is to promote the recognition of these women and given their vulnerabilities experienced on various levels, this recognition must be wide and include recognition as workers, citizens and members of society that must be afforded human dignity on all levels. The position of the three categories of women workers was also considered in two jurisdictions, namely India and Brazil to distil best practices with reference to these workers. The research question of this study is: How can labour law and social protection measures provide vulnerable women workers in the informal economy with the appropriate protection to ultimately give effect to decent work? The main inquiry of this thesis, therefore, is to explore the issue of extending labour and social protection to these workers through the extension of existing labour and social security rights; including, where necessary, the design and implementation of innovative and tailor-made solutions.
Keywords: Decent work; Discrimination; Domestic worker; Gender equality; Informal economy; Informal trader; Labour and social protection; Social assistance; Social justice; Social security; Tailor made provisions; Waste pickers; Women; Worker organisations

The impact of threshold agreements on the organisational rights of minority trade unions - Esitang, Temogo Geoffrey (University of Pretoria, 2017)
The rights of freedom of association, to organise and to bargain collectively are recognised internationally and form part of the constitutional framework of progressive and democratic states. The full enjoyment of these rights by trade unions often is hindered by the imbalance in the power relations between the employer and the representatives of the workers, hence the need for statutory intervention. The Labour Relations Act 66 of 1995 (LRA of 1995) postulates a collective bargaining regime which is voluntarist in nature and strengthens its effectiveness through a set of organisational rights and the right to strike. Incidentally, the current statutory framework for the enjoyment of organisational rights has had a direct impact on the enjoyment of the right to freedom of association and the right to organise. It is accepted that possession of the right to collective bargaining is internationally recognised as the basis of the authority to set thresholds of representivity in the workplace. The organisational rights framework in this context has been directly impacted upon. It is this direct impact that necessitates an enquiry to determine whether South Africa’s framework on the acquisition of organisational rights conforms to international standards set by the ILO and the Constitution, 1996. This thesis argues that the policy choice of the South African labour relations system in respect of some of the consequences of majoritarianism insofar as representation in individual cases is concerned does not necessarily foster the ideals of the Constitution, 1996 and the principles of international labour standards. The model of democracy as envisaged in the Constitution, 1996 is not one that promotes exclusivity. However, the effect of section 18 of the LRA of 1995, which allows threshold agreements, arguably may foster such exclusivity in the workplace. This situation has resulted in industrial democracy being a terrain of endless conflict between employers and labour, even more among trade unions themselves. As a result, the rivalry between unions in workplaces is exacerbated. The original intent behind the organisational rights of trade unions and their right to strike was to bolster their capacity to bargain collectively. It was meant to get them to focus on collective bargaining gains they can secure and to bargain more effectively. However, the current framework that favours majority trade unions has the effect of minority trade unions generally finding their existence threatened and their being systematically excluded from the acquisition of organisational rights. This study questions the power of majority trade unions to enter a collective agreement with an employer in the workplace and set unjustifiable thresholds of representivity in respect of organisational rights. This arrangement creates a hurdle in respect of the provisions of the LRA that seek to promote industrial democracy, the enjoyment of the rights to freedom of association, to organise and to engage in collective bargaining. Recent amendments to the LRA of 1995 are an attempt to mitigate the effect of sections 18 and 20 on the enjoyment of organisational rights. The CCMA, inter alia, has been granted powers to grant organisational rights to trade unions that do not meet the set threshold in terms of the empowering provisions of the LRA of 1995 if they meet certain requirements. However, these amendments do not go far enough to prevent employers and majority trade unions from continuing to set unjustifiable thresholds that can have potential to replace the determinations of the CCMA. Therefore, the study discusses the question whether the provision in the LRA of 1995 on the setting of thresholds of representivity for the acquisition of organisational rights and the concomitant amendments are in line with the democratic model envisaged by the Constitution, 1996 and to international labour standards which recognise the rights to freedom of association of minority trade unions. This research concludes by advancing recommendations pertaining to threshold agreements and the rights of minority trade unions and to what extent it is justifiable to permit them to enjoy them.
Keywords: Collective bargaining; Employer; Employeur; Labour Relations Act; Representatives workers

Identification of the parties to the employment relationship: An appraisal of teleological interpretation of statutes - Van Staden, Marthinus Jacobus (University of Pretoria, 2017)
The study, entitled “Identification of the parties to the employment relationship: an appraisal of teleological interpretation of statutes”, is a legal-interdisciplinary doctrinal investigation situated within the fields of labour law and the interpretation of statutes. It concerns itself with the proper interpretation of labour legislation in general and the interpretive question as to who should be party to the employment relationship in particular, within the context of the advent of constitutionalism and the proliferation of and the increase in the importance of labour legislation. In law, meaning-generation is a function of statutory interpretation and every application of a text to particular circumstances entails interpretation. The protection extended by labour legislation is only extended to those persons who are defined as “employees”. The study describes the teleological model of statutory interpretation, which aims to give effect to the purpose of a legislative provision in light of constitutional values. The study explores the five elements of (teleological) interpretation that should be considered when interpreting concepts such as “employee”: the text, the context, the telos (or values), the history and the comparative dimension. The chief findings of the study includes: that legislation has become an indispensable source of contemporary labour law; that the courts have adopted a teleological approach to the interpretation of statutes; that the courts have, in interpreting the term “employee”, adopted a teleological approach to the interpretation of statutes; and that the interpretations advanced by the courts have not had the profound effect envisaged by the Constitution on the transformation of society.
Keywords: Employment relationship; Labour law; Parties

Force Majeure, Change of Circumstances and Termination of Contract - Han, Shiyuan (Journal of Law, Society and Development, 2016)
It is impossible to draw a distinct line between force majeure and change of circumstances, because the two overlap. In order to regulate both force majeure and change of circumstances, the United Nations Convention on Contracts for the International Sale of Goods (CISG) has adopted a unified model in article 79, whereas Chinese law adopts a dual model by treating them as different things and regulating them in different articles. Where the purpose of a contract becomes impossible to achieve because of a force majeure and both the CISG and Chinese Contract Law (the CCL) adopt the same model of termination of the contract, the contract should be terminated by one party with a notice to the other party instead of ipso facto avoidance. In a case of a change of circumstances, in order to terminate the contract, both the CISG and the CCL actually follow the path of raising an action by a notice of avoidance or termination to theother party. Both approaches have their merits and demerits but the differences between them in practice are not as large as presumed. Where force majeure and change of circumstances overlap each other, possible ways for termination of the contract are for a party either to choose their preferred solution or to follow the lex specialis derogat generali. The latter way is preferred in this article; and while in an action for termination the judge may balance the interests of both parties in making a final decision, the uniform application of the law, the safety of the transaction and the fairness of the judgment may be ensured in so doing.
Keywords: CISG; Change of circumstances; Chinese Contract Law; Force majeure; Gestaltungsklagerecht; Termination

Protection of agency workers in South Africa : an appraisal of compliance with ILO and EU Norms - Aletter, Candice Joy (University of Pretoria, 2016)
This thesis is a policy-based study of the regulation of agency work in South Africa. It is set against the contextual background of a recent legislative overhaul and an increase in the number of precarious workers. The study aims to appraise the extent to which the South African regulatory framework complies with international norms in respect of agency work. The research considers how German and Namibian regulation might improve the current model of the regulation of agency work in South Africa. The study identifies the purpose of labour law in South Africa as offering diversified rights as well as being economic in nature. The premise upon which the thesis is based is a social justice approach to the function of labour law. An analysis of ILO and EU regulations on agency work is conducted, and identifies a combined list of norms in respect of the protection of agency workers. South Africa?s labour law policy approach is explored together with the amended regulation on agency work. A comparison is drawn with foreign countries? regulations and policy approaches: the appraisal identifies shortcomings in South Africa?s regulatory model. The study focuses on the evolutionary improvement of agency workers? protection based on international approaches. The research culminates by formulating an amended model for the regulation of agency work in South Africa, in which these proposed adaptations seek to remedy the shortcomings which were observed in the appraisal process.
Keywords: Agency work; EU Regulations; ILO; Labour law; South Africa

Regional Labour Standards in the SADC: Is It Possible, Given the EU Experience? - Smit, Paul (Journal of Law, Society and Development, 2015)
Globalisation and the increasing movement of capital and labour across international borders, with the exception of migrant workers who are facing major obstacles due to immigration laws, are creating a situation where laws in general and labour laws in particular are acquiring an international character. International bodies such as the United Nations, the International Labour Organisation and the European Union have adopted various international norms and standards to which most countries have agreed and which have established minimum international standards for basic universal human rights and worker rights. The Southern African Development Community is a transnational organisation that has also adopted certain basic norms and standards in its Treaty, Charter on Fundamental Social Rights and various protocols that are applicable to all citizens within the Community. In this contribution, the concept of transnational labour relations is considered. The different international approaches towards transnational labour relations are evaluated, as is the manner in which the European Union approached the integration of regional labour standards. The author seeks to establish what the Southern African Development Community can learn from the European Union’s experience and in what way a transnational labour relations system or regional labour standards regime for the Southern African Development Community can be established.
Keywords: Regional integration; Transnational labour relations (TNLR); international law; labour rights; regional labour standards; social rights

Employee participation and voice in companies: a legal perspective - Botha, Monray Marsellus (North-West University, 2015)
Recently, South African company law underwent a dramatic overhaul through the introduction of the Companies Act 71 of 2008. Central to company law is the promotion of corporate governance: companies no longer are accountable to their shareholders only but to society at large. Leaders should direct company strategy and operations with a view to achieving the triple bottom-line (economic, social and environmental performance) and, thus, should manage the business in a sustainable manner. An important question in company law today: In whose interest should the company be managed? Corporate governance needs to address the entire span of responsibilities to all stakeholders of the company, such as customers, employees, shareholders, suppliers and the community at large. The Companies Act aims to balance the rights and obligations of shareholders and directors within companies and encourages the efficient and responsible management of companies. The promotion of human rights is central in the application of company law: it is extremely important given the significant role of enterprises within the social and economic life of the nation. The interests of various stakeholder groups in the context of the corporation as a “social institution” should be enhanced and protected. Because corporations are a part of society and the community they are required to be socially responsible and to be more accountable to all stakeholders in the company. Although directors act in the best interests of shareholders, collectively, they must also consider the interests of other stakeholders. Sustainable relationships with all the relevant stakeholders are important. The advancement of social justice is important to corporations in that they should take into account the Constitution, labour and company law legislation in dealing with social justice issues. Employees have become important stakeholders in companies and their needs should be taken into account in a bigger corporate governance and social responsibility framework. Consideration of the role of employees in corporations entails notice that the Constitution grants every person a fundamental right to fair labour practices. Social as well as political change became evident after South Africa's re-entry into the world in the 1990s. Change to socio-economic conditions in a developing country is also evident. These changes have a major influence on South African labour law. Like company law, labour law, to a large extent, is codified. Like company law, no precise definition of labour law exists. From the various definitions, labour law covers both the individual and collective labour law and various role-players are involved. These role-players include trade unions, employers/companies, employees, and the state. The various relationships between these parties, ultimately, are what guides a certain outcome if there is a power play between them. In 1995 the South African labour market was transformed by the introduction of the Labour Relations Act 66 of 1995. The LRA remains the primary piece of labour legislation that governs labour law in South Africa. The notion of industrial democracy and the transformation of the workplace are central issues in South African labour law. The constitutional change that have taken place in South Africa, by which the protection of human rights and the democratisation of the workplace are advanced contributed to these developments. Before the enactment of the LRA, employee participation and voice were much-debated topics, locally and internationally. In considering employee participation, it is essential to take due cognisance of both the labour and company law principles that are pertinent: the need for workers to have a voice in the workplace and for employers to manage their corporations. Employee participation and voice should be evident at different levels: from information-sharing to consultation to joint decision-making. Corporations should enhance systems and processes that facilitate employee participation and voice in decisions that affect employees. The primary research question under investigation is: What role should (and could) employees play in corporate decision-making in South Africa? The main inquiry of the thesis, therefore, is to explore the issue of granting a voice to employees in companies, in particular, the role of employees in the decision-making processes of companies. The thesis explores various options, including supervisory co-determination as well as social co-determination, in order to find solutions that will facilitate the achievement of employee participation and voice in companies in South Africa.
Keywords: CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Corporate law; Disputes; Economic democracy; Employee participation; Empowerment; Fairness; Industrial democracy; Joint decision-making; Labour law; Matters of mutual interest; Shareholders; Social justice; Stakeholders; Workplace forums

Labour rights and working conditions in corporate codes of conduct: an assessment of the legal dimension, in different national contexts, of selected multinational corporations’ corporate social responsibility commitments - Tiemeni, Thierry Galani (University of the Western Cape, 2015)
At the heart of this thesis is the notion of Corporate Social Responsibility (CSR), an innovative concept deep-rooted in the globalisation phenomenon. The notion of CSR entails the much-debated duty of businesses, not only to comply with international and local standards in terms of, inter alia, labour rights and working conditions, human rights and environmental protection, but also to be at the forefront of voluntary and uplifting actions geared toward addressing societal issues and concerns. For corporations, it is about moving from the traditional approach of business as an activity with the sole purpose of realising profit towards acknowledging the need to integrate societal and environmental issues and concerns into their business purposes. The thesis examines selected multinational corporations’ (MNC) approaches to CSR as contained in their codes of conduct, in an effort to reach a comprehensive understanding of the purpose, interest and practices of businesses engaging in CSR activities. Particular attention is given to the analysis of labour orientated measures implemented by selected MNCs as they undertake to voluntarily act as proponents of the theory of the necessity of socially responsible businesses. The aim is to comparatively assess the legal dimension and the relevance, in different countries, of these MNC CSR commitments. The first part of the thesis is theoretical and has the purpose to present a comprehensive analysis of CSR against the current legal framework, at a global scale and within the context of selected countries. The thesis will explore the notion of CSR in order to present its definition and characteristics, briefly retrace its history, differentiate it from related and/or similar concepts, and finally assess the extent of its introduction and adaptation into various national and international institutional frameworks. Even though initially addressing the issue of CSR in the current legal framework as a whole, the scope of the thesis will ultimately be reduced to focus only on labour-related aspects of CSR. The aim of the thesis is to assess MNC’s CSR commitments, and subsequently highlight the interaction between CSR, labour and employment legal frameworks (at national and international level) and the effective implementation of labour rights and working conditions as observed in the context of different countries. More importantly, the thesis will also include a comparative analysis of CSR principles included in selected MNC codes of conduct, in order to assess the extent of their compliance with national labour legislation, international labour standards, as well as the standards and principles set by national and international CSR instruments and institutions. The purpose of such an exercise is to thoroughly assess the impact of a national context - in terms of national legal, economic, social and industrial framework - on the legal dimension, and the relevance of MNCs CSR commitments. A crucial argument developed in the thesis refers to the fact that MNC codes of conduct may have the potential to impact on labour rights and working conditions of a MNC across the different countries into which the MNC operates. Finally, considering the fact that as a topic CSR is a potentially controversial subject, it is necessary to point out, from the onset, that the thesis engages with the subject from a critical perspective. The approach therefore entails critically analysing and discussing MNC commitments and practices as observed in different countries, so as to be able to ascertain and comprehend the impact of a national context on the content, the relevance and the legal dimension of MNC codes of conducts
Keywords: Code of conduct; Corporate Social Responsibility; Labour rights; Multinational corporations; Working conditions

Employees Contract of Employment and Wrongful Dismissal From Service - Ugbele, Sunday; Utobo, O. J. (African Journal of Politics and Administrative Studies, 2014)
Contract of employment was long acknowledged as a subject of genuine and voluntary agreement whose construction or determination should be founded on due notice of the parties thereto. Action for wrongful dismissal would lie if an employment was disturbed, interfered or meddled with, in defiance of the rights of the parties under the contract. The objective of this study was, among others, to determine what constituted a valid contract of employment and remedies for wrongful dismissal. The qualitative and documentary method of data collection was adopted by reference to relevant literature and statutory authorities. From the data gathered, and content analyzed, we found that no law could foreclose an employment from determination, nor could an irregular or wrongful dismissal stand. It was recommended, inter alia, that beside the need to repeal the Public Officers (Protection) Act, both the employer and employee should, in their official dealings, respect the sanctity of their contract, and permit reasonable future modifications thereto as could lawfully enhance the life of the contract and their legitimate desires.

New Frontiers on Legal Enforceability of Collective Agreements in Nigeria - Zechariah, Matthias (Current Jos Law Journal, 2013)
The objectives of this research paper are: to examine the status of collective agreements under the common law; highlight impacts of statutory intervention on common law perception of collective agreements, and discuss how the National industrial Court (NIC) and the Constitution of the Federal Republic of Nigeria 1999 (as altered) have broadened the horizon of enforceability of collective agreements in Nigeria. Reliance is placed principally on statutes, judicial decisions, textbooks written by learned authors as well as international best standard and practices championed by the International Labour Organization (ILO) and practices in some foreign jurisdictions. The ﬁndings of the research were that under the common law, collective agreements are ordinarily not binding, they are considered as a ‘gentleman's agreement‘, a product of a trade unionist's pressure, binding only in honour or on the goodwill of the parties thereto, unless and until it is incorporated expressly or impliedly into the contract of employment. However, statutory intervention has slightly altered the common law notion of collective agreements, e.g. where the Minister of Labour and Productivity is empowered to declare, by order, that part or the whole of an agreement deposited in his ofﬁce is binding on the parties. Furthermore, with the enactment of the NIC Act and the listing of the NIC in the 1999 Constitution as a superior court of record (following the alteration of the Constitution, necessitated by the N.U.E.E. V BPE case), the Court now has exclusive jurisdiction to adjudicate on a wide range of labour matters, industrial relations and application of international best practices such as the standard and principles of the International Labour Organization (ILO), and practices in foreign jurisdictions. It has been argued that the enforceability of collective agreements is in tandem with international best practices, which the NIC can readily give effect to, if it is pleaded and established/ proved as a fact. This has invariability expanded the frontiers of enforceability of such agreements. Therefore, the common law position on the status of collective agreements has been rendered otiose and obsolete, giving way to the sparkling provisions of enforceability guaranteed by the NIC Act and the Constitution respectively. Notwithstanding, it is highly recommended that parties to a collective agreement should expressly state their intention whether or not to be bound; the duration of the agreement should be stated and whether, and when, it should, be reviewed; experts and other stakeholders should be properly consulted before an agreement is entered into; an arbitration clause may be included in case a party breaches its own part of the agreement. Industrial democracy ought to be promoted in all sectors. Strikes and lock outs should be used only as a last resort for enforcing compliance with a collective agreement, because these industrial actions cause devastating effects on the economy and on the lives of the citizenry generally.

Disability, discrimination and equal opportunities : a comparative labour law study - Harmse-Truter, Laurentia (University of Johannesburg, 2012)
This study aims to investigate the different ways in which the position of people with disabilities can be addressed. Antidiscrimination legislation can play a very important role. Efforts to create equal opportunities must, however, not be limited to legislative initiatives and policy declarations. There is an urgent need for education and training of this minority group. 7 Systematic efforts to heighten public awareness of civil rights and in particular the recognition of the rights of the disabled community are imperative. This study aims to bring home the truth that "disability rights are an idea and ideal whose time has come. ,, When addressing the issue of disability discrimination (or for that matter any kind of discrimination) several principles need to be addressed, the most important being the following: The meaning of the concept of "equality" needs to be established. The fact that all people are equal, does not necessarily mean that all people must be treated the same. When speaking about disability discrimination one must know who forms part of the protected class. For that reason the first issue that must be addressed is the definition of "disability": This leads to the next question, namely which individuals should be protected by anti-discrimination laws and should they benefit from affirmative action measures? What is meant by the term "discrimination"? Is it at all permissible to distinguish between groups of people and, if so, when and which standards are to be applied? What role can anti-discrimination legislation fulfil in the struggle for equality? When dealing with anti-discrimination legislation, what is required in order to prove discrimination and what remedies must be available to an aggrieved party? Normally, in case of criminal action proof is required beyond reasonable doubt and in case of civil action on the balance of probabilities. 10 Civil action offers more effective remedies, but should it be punitive in nature (by awarding damages to the aggrieved party) or non-punitive (by putting the aggrieved party in his/her "rightful place")? What sort of enforcement mechanism is needed? Is it a task for the ordinary tribunals or rather a special body created for that purpose? What defences should be available to an employer accused of discriminatory practices? Who should benefit from enforcement? Only the individual victim or all members of that group? Is anti-discrimination legislation sufficient or is something in addition called for? If positive measures are required, what form must these measures take? This study will address these questions specifically with relation to people with disabilities.The "equality principle" will first be studied. Thereafter the concept of "disability" will be defined. There is a movement away from a medical model of disability towards a social model that takes account of the disabling effects of attitudes and structural barriers on the position of disabled people. Then the concept of "discrimination" will be addressed. Discrimination has many different forms and can take place in different contexts In the following chapter possible solutions to the problem of disability discrimination will be raised. Thereafter follows an important comparative analysis of different jurisdictions on international, supra-national and national level. Different jurisdictions have reached different stages in addressing this problem. The factual analysis of each jurisdiction will include the existence of any anti-discrimination legislative measures, the scope of the protected class, applicable employment provisions, defences available to employers, and the success achieved in addressing the problem. The contentious issue of affirmative action measures will also be addressed. By drawing inferences from the comparative study, suggestions will be made for future developments in South Africa. The conclusion is reached that it is imperative for South Africa to draft disability anti-discrimination legislation that takes account of the needs of this minority group. Legislative initiatives, however, are not enough and must be supported by various programmes aimed at the disabled themselves and the community that they live in. Only then can human rights become a reality also for people with disabilities.
Keywords: Comparative law; Discrimination; Employment; Labour law; People with disabilities

The legal implications of harmonising labour laws in the Southern African Development Community (SADC) region - Okharedia, Akhabue Anthony (University of South Africa, 2012)
The purpose of this research is to explore the need for, and the legal implications of, harmonising labour laws in the Southern African Development Community (SADC). Chapter One highlights a number of factors that call for the harmonisation of labour laws in the SADC region and discusses some of the reasons why labour laws are not well developed in the region. The influence of globalisation on labour standards in southern Africa and the influence of regionalism on the harmonisation of labour laws are discussed at length. The inference that could be drawn from this discussion is that for a regionalisation process in southern Africa to be successful, there is an urgent need to harmonise the region’s labour law system. This thesis confirms that Southern Africa has many lessons to learn from the regional harmonisation of labour law in the European Economic Community and the current European Union. The implementation of international labour standards in southern Africa is investigated. The main areas examined include (1) freedom of association, (2) collective bargaining, (3) forced labour and (4) discrimination. The findings of this investigation show that there is no uniformity in the implementation of International Labour Organisation (ILO) standards in the SADC region and, therefore, it is recommended labour law should be harmonised in terms of ILO standards. In respect of the benefits to be derived from the harmonisation process, an empirical investigation was conducted in the SADC region and the following is recommended: the harmonisation of labour law in the SADC region will help with the implementation of ILO standards, protection of workers against the economic power of employers in the workplace and maintaining similar benefits for migrants in the region.
Keywords: Child labor; Collective bargaining; Compulsory labour; Discrimination in employment; Discrimination in the work environment; Droit du travail; Forced labour; Freedom of association; Harmonisation; International Labour Organization; International Labour Standards; Labour law; SADC

The Protection of Privacy in the Workplace: A Comparative Study - Gondwe, Mimmy (Stellenbosch University, 2011)
The importance of privacy lies in the fact that it represents the very idea of human dignity or the preservation of the ‘inner sanctum’. Not surprisingly, however, operational concerns of employers and technological developments combine continuously to challenge the preservation of privacy in the workplace. Employees the world over are exposed to numerous privacy invasive measures, including drug testing, psychological testing, polygraph testing, genetic testing, psychological testing, electronic monitoring and background checks. Hence, the issue at the heart of this dissertation is to determine to what extent privacy is protected in the South African workplace given advancements in technology and the implications (if any) for the right to privacy as such. A secondary aim of the dissertation is to attempt to provide a realistic balance between the privacy concerns of employees and the operational needs of employers in this technological age. As such the main focus of dissertation falls within the sphere of employment law. In order to provide an answer to the research issue discussed above, the dissertation addresses five ancillary or interrelated issues. First, the broad historical development of the legal protection of privacy is traced and examined. Second, a workable definition of privacy is identified with reference to academic debate and comparative legislative and judicial developments. Third, those policies and practices, which would typically threaten privacy in the employment sphere are identified and briefly discussed. Fourth, a detailed evaluation of the tension between privacy and a number of selected policies and practices in selected countries is provided. More specifically, the dissertation considers how these policies and practices challenge privacy, the rationale for their existence and, if applicable, how these policies and practices – if necessary through appropriate regulation – may be accommodated while simultaneously accommodating both privacy and the legitimate concerns of employers. The selection of these practices and policies is guided by two considerations. At the first level the emphasis is on those challenges to privacy, which can be traced back to technological developments and which, as such, foster new and unique demands to the accommodation of privacy in the workplace. The secondary emphasis is on those policies, which are representative of the fundamental challenges created by new technologies to privacy. To effectively address the above issues the dissertation uses the traditional legal methodology associated with comparative legal research, which includes a literature review of applicable law and legal frame work and a review of relevant case law and a comparative study of selected foreign jurisdictions.
Keywords: Privacy infringements; Privacy protection; Right of privacy

Public employment and the relationship between labour and administrative law - Loots, Barbara Evelyn (University of Stellenbosch, 2011)
The focus of this study is the rights-based normative overlap of labour and administrative law in public employment. As the judiciary appeared to be unable to agree on a unified approach to the application of the rights to fair labour practices and just administrative action to public employment, it was clear that the complexity and multi-dimensional character of the debate required analysis of existing approaches to the regulation of the public employment relationship. The following initial research question was formulated: To what extent does (and should) the constitutionalised rights to fair labour practices (s 23) and just administrative action (s 33) simultaneously find application in the regulation of public employment relationships? In answering this question, certain realities had to be acknowledged, the most important being that the debate in question jurisprudentially revealed itself to be a jurisdictional turf-war between the Labour and High Courts, rather than proper consideration of the relevant substantive arguments and underlying normative considerations. This called for an additional dimension to be added to the research question, namely consideration of the extent to which the ss 23 and 33 rights are informed by variable and possibly different normative principles and whether these rights allow for cooperative regulation of public employment in accordance with the doctrine of interdependent fundamental rights. This became the primary focus of the study. In an attempt to simplify the debate, a deliberate decision was taken to limit the scope of the normative study to South Africa with its own historic influences, structures and constitutional considerations. The study shows that both labour and administrative law (as constitutionally informed) share concern for equity-based principles. This is evident from the flexible contextually informed perspectives of administrative law reasonableness in relation to labour law substantive fairness, as well as a shared concern for and approach to procedural fairness. Once simplified, and in the absence of any undue positive law complexity, the public employment relationship, at both a normative and theoretical level, furthermore shows no substantive status difference with private employment relationships. It is, however, accepted that there are job and sector-specific contextual differences. In the absence of substantive normative conflict between these branches of law and in the absence of a fundamental (as opposed to contextual) difference between public and private employment, there appears to be no reason to ignore the constitutional jurisprudential calls for hybridity, otherwise termed the doctrine of interdependence. The idea of normatively interdependent rights expresses the Constitution’s transformative vision (through the idea of flexible conceptual contextualism) and recognises that human rights may overlap. This also means that where such overlap exists, rights should be interpreted and applied in a mutually supportive and cooperative manner that allows for the full protection and promotion of those rights. In giving expression to the interdependent normative framework of constitutional rights, these norms (absent any substantive rights-based conflict) should then be used by the judiciary as an interpretative tool to align specific labour law and general administrative law in the regulation of public employment relationships.
Keywords: Administrative law; Employment law; Labour law